BREAK EVENT POINT PADA PENYUSUNAN ANGGARAN OPERASIONAL DI UNIVERSITAS XYZ - Amelia, Hesti Zia; Kusuma, Indra Cahya (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2024)
This study aims to determine the components, calculations, and magnitude of the break event and shutdown point in preparing the budget at XYZ University. This research is a quantitative descriptive research method. Calculating the BEP in compiling a university’s operating budget is very important so that it can be known how many students are accepted to reach the breakeven point (BEP).